AB0112 Differences in Serum Biomarker Profiles of Anti-Citrullinated Protein Antibody-Positive and Anti-Citrullinated Protein Antibody-Negative Rheumatoid Arthritis. (9th June 2015) - Novikov, A.; Aleksandrova, E.; Karateev, D.; Lutchihina, E.; Popkova, T.; Cherkasova, M.; Nasonov, E.
Abstract : Background: Comparative data on serum biomarker profile in anti-citrullinated peptide/protein antibody positive (ACPA+) and ACPA negative (ACPA-) rheumatoid arthritis (RA) patients are scarce. Objectives: Our aim was to analyze serum levels of proteomic biomarkers in patients with RA according to the presence or absence of ACPA. Methods: We examined serum samples from 118 pts: 37 with early RA (<6 months disease duration, median and interquartile range (25th–75th percentile) of age 51 (41-62) years, 76% female, 79% ACPA+); 81 with established RA (>6 months disease duration, 49 (41-57) years, 88% female, 79% ACPA+). Patients were defined as ACPA - if serum was negative to three different ACPAs (second anti-CCP2, anti-MCV, anti-keratin antibodies). Anti-CCP2, anti-MCV, IgA RF was measured by ELISA; anti-keratin antibodies by indirect immunofluorescence assay; IgM RF by immunonephelometry. Cytokine analyses were performed with multiplex technology (Human Grp I Cytokine 27-plex panel for BioPlex 200). Results: ACPA+ with early RA had significantly higher levels of IgM RF, IL-15, G-CSF, with established RA – IgM/IgA RF, TNF-α, IL-15, -1ra, -2, -5, -9-10, -12, eotaxin, GM-CSF, MCP-1 than ACPA pts. Conclusions: ACPA+ patients had higher levels of RF, anti- and pro-inflammatory cytokines, colony-stimulating factors and chemokines than ACPA- patients. Disclosure of Interest: None declared